Sleep health and its implications in First Nation Australians: A systematic review - Sarah Blunden; Stephanie Yiallourou; Yaqoot Fatima (Elsevier, 2022)
Summary: Understanding the state of sleep health in First Nations Australians offers timely insight into intervention and management opportunities to improve overall health and well-being. This review explored the determinants and burden of poor sleep in First Nations Australians. A systematic search was conducted to identify studies published until August 2020 in First Nations Australian adults. Nine studies (n = 2640) were included, three in community settings, six in clinical populations. Across studies compared with non-Indigenous people, 15-34% of First Nations Australians experience less than recommended hours (<7 h/night), 22% reported fragmented, irregular, and unrefreshing sleep with a high prevalence of OSA in clinical populations (39-46%). Findings show First Nations Australians are significantly more likely to report worse sleep health than Non-Indigenous Australians in all measured domains of sleep. Co-designed sleep programs and service delivery solutions are necessary to ensure timely prevention and management of sleep issues in First Nations communities which to date have been underserved. Funding: No external funding was provided for this work.